"It's a very difficult question isn't it?" Researcher, interpreter and research participant negotiating meanings in an education research interview. (November 2013) - Andrews, Jane
Abstract : Writers within Applied Linguistics and beyond have argued for research papers using interview methods to acknowledge all participants' contributions to that data for example, Kvale and Brinkmann, and Mann. When research encounters involve participants who do not all share each other's languages, interpreters are often brought in as mediators and the issues of how to represent the research encounter and the data transparently increase. Temple and Edwards have called for interpreters within research to be recognised as co‐researchers given their impact on co‐constructing the interaction. In this paper, data from a single education research interview is explored using insights from sociocultural theory and interactional sociolinguistics in order to develop understandings of how knowledge was co‐constructed in this instance of a multilingual research encounter.